Development of Аntarctic protected areas: mathematical forecast for 2020 - Kuzko, O.V.; Fedchuk, A.P.; Savchenko, V.V. (Український антарктичний журнал, 2015)
This paper discusses the growing dynamics of the increasing of the amount and especially the Antarctic Specially Protected Areas (ASPA) and the Antarctic Specially Managed Areas (ASMA). This dynamics is a reflection of the sustainable environmental imperative in the national interests of the Antarctic Treaty Parties. This dynamics is analyzed using the Richardson’s model, which was used by Thomas L. Saaty for the analysis of the arms race dynamics in the twentieth century. Using this model made it possible to estimate the expected of the ASPA and ASMA amount and areas in the near future. So in 2020 it is expected to increase the total areas of ASPA and ASMA up to 103,700 km2 (which is comparable to the Iceland area). The question of the accuracy increasing of the used model and the accuracy of the quantitative characteristics is discussed. The obtained quantitative characteristics will provide the policy makers and national Antarctic program managers by the additional arguments for decision-making on the further management of the human activities and nature conservation in the Antarctic. Among the general public obtained characteristics will contribute to the better understanding of the development trends of the international legal regime of the Antarctic.